Kajian tentang pemahaman guru sekolah dasar PJOK terhadap permainan tradisional - Nurani, Winda; Ekowati, Ekowati (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2022)
This study aims to determine how much PJOK elementary school teachers understand traditional games. This research method is quantitative descriptive research. Data collection was obtained by using a questionnaire totaling 50 questions which were tested on all PJOK elementary school teachers in West Bekasi District, totaling 36 people. Based on the research results, it is known that the understanding of elementary school PJOK teachers on traditional games in the West Bekasi District is very high. This is evidenced by the results of the study which showed that 7 respondents had a very low understanding, 1 respondent had a low understanding, 1 respondent had a moderate understanding, and 27 respondents had a very high understanding.